FDG–PET imaging, EEG and sleep phenotypes as translational biomarkers for research in Alzheimer's disease. (20th July 2011) - Platt, Bettina; Welch, Andy; Riedel, Gernot
Abstract : The lack of reliable translational procedures applicable to both patients and experimental models are a major obstacle for the advancement of basic research as well as for the development of therapeutics. This is particularly relevant to neurodegenerative disorders such as AD (Alzheimer's disease), where the predictive validity of animal models and procedures applied preclinically have met with little success. Two approaches available for human diagnostics are currently experiencing major advancements in preclinical research: in vivo imaging using MRI (magnetic resonance imaging) or PET (positron-emission tomography) and recordings of brain electrical activity via surface EEG (electroencephalogram). The present paper reviews the results obtained so far in rodent AD models, and summarizes advantages and disadvantages of such procedures.